Mediastinal ganglioneuroma: An incidentaloma of childhood - Ram Mohan Shukla; Biswanath Mukhopadhyay; Madhumita Mukhopadhyay; Kartik Chandra Mandal (Indian Journal of Medical and Paediatric Oncology)
Ganglioneuroma is a rare benign neurogenic tumor which represents the final maturation stage of neuroblast tumors. Here, we are discussing an interesting case of incidentally detected posterior mediastinal ganglioneuroma which should be kept in mind when dealing with any child with respiratory distress.